Effects of static and PNF stretching on joint position sense and range of motion after a fatigue protocol in professional male soccer players - Farshidi, B.; Daneshjoo, A.; Sahebozamani, M.; Konrad, A. (Medicina dello Sport, 2022)
BACKGROUND The aim of this study was to compare the effects of a single bout of static stretching (SS) or proprioceptive neuromuscular facilitation (PNF) stretching of the knee flexors on joint position sense (JPS) and knee extension range of motion (ROM) after a soccer-specific fatigue protocol in young male professional soccer players.